Prevalence of antibiotic (ß-lactams, tetracycline, metronidazole, erythromycin) resistance genes in periodontic infections - Freitas, Daniel (2019)
Objective: Porphyromonas gingivalis and Prevotella intermedia are thought to be pathogens in adult periodontitis. Antibiotherapy is usually needed in the treatment of periodontitis being often prescribed empirically. To allow prescription of a specific antibiotic treatment, identification of resistance genes should be performed. The aim of this study was the identification of the presence of TetM, TetQ, TEM, cfxA, MefA, ErmB and Nim resistance genes in previously identified P. intermedia and P. gingivalis isolated from samples collected from periodontal infections. Method: PCR was used for the identification of TetM, TetQ, TEM, cfxA, MefA, ErmB and Nim resistance genes in strains isolated from samples collected from periodontal infections. Results: It was seen that 8% of isolates had one of the tested tetracycline resistance genes. A total of 32% of β-lactamases resistance genes was observed in isolated strains. It was also observed that 2% of isolates had one of the analysed erythromycin resistance genes. None of the isolates showed the presence of the metronidazole resistance gene. Conclusions: Most strains harboring β-lactamase resistance genes had been previously identified as P. intermedia. No tetracycline resistance gene and a very low percentage of β-lactamase resistance genes were observed in P. gingivalis strains.